Blind Spots of Knowledge in Shakespeare and His World : A Conversation - Mukherji, Subha (Book collections on Project MUSE., 2019)
A "blind spot" suggests an obstructed view, or partisan perception, or a localized lack of understanding. Just as the brain "reads" the "blind spot" of the visual field by a curious process of readjustment, Shakespearean drama disorients us with moments of unmastered and unmasterable knowledge, recasting the way we see, know and think about knowing. Focusing on such moments of apparent obscurity, this volume puts methods and motives of knowing under the spotlight, and responds both to inscribed acts of blind-sighting, and to the text or action blind-sighting the reader or spectator. While tracing the hermeneutic yield of such occlusion is its main conceptual aim, it also embodies a methodological innovation: structured as an internal dialogue, it aims to capture, and stake out a place for, a processive intellectual energy that enables a distinctive way of knowing in academic life; and to translate a sense of intellectual "community" into print